2007
DOI: 10.1055/s-2007-984404
|View full text |Cite
|
Sign up to set email alerts
|

Error Reduction When Prescribing Neonatal Parenteral Nutrition

Abstract: A neonatal intensive care unit audit of 204 parenteral nutrition (PN) orders revealed a 27.9% PN prescribing error rate, with errors by pediatric residents exceeding those by neonatal nurse practitioners (NNPs) (39% versus 16%; P < 0.001). Our objective was to reduce the PN prescribing error rate by implementing an ordering improvement process. An interactive computerized PN worksheet, used voluntarily, was introduced and its impact analyzed in a retrospective cross-sectional study. A time management study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 22 publications
0
31
1
Order By: Relevance
“…Taheri et al showed that the main causes of error in medication prescription in NICU from the nurses' perspective included limited number of staff (9.26%), heavy work load (17.6%), physical and psychological fatigue (14.3%), and hustle and bustle of the ward (12.6%), followed by other causes (TAHERI, NOORIAN, RASSOULI, & KAVOUSI). This is while, in Al-Rafay's research, the overall practice of the nurses after the completion of training course showed a significant difference (p<0.001), which was inconsistent with this study Brown et al (2007) found that the PN practice score of the nurses was higher than that of pediatric residents. After educational intervention, practice scores of the residents and nurses reached the same level, indicating the effect of such intervention on the practice.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Taheri et al showed that the main causes of error in medication prescription in NICU from the nurses' perspective included limited number of staff (9.26%), heavy work load (17.6%), physical and psychological fatigue (14.3%), and hustle and bustle of the ward (12.6%), followed by other causes (TAHERI, NOORIAN, RASSOULI, & KAVOUSI). This is while, in Al-Rafay's research, the overall practice of the nurses after the completion of training course showed a significant difference (p<0.001), which was inconsistent with this study Brown et al (2007) found that the PN practice score of the nurses was higher than that of pediatric residents. After educational intervention, practice scores of the residents and nurses reached the same level, indicating the effect of such intervention on the practice.…”
Section: Discussioncontrasting
confidence: 94%
“…In this regard, he compared his research data with those of Brown's educational intervention in relation to the use of inactive computerized sheets to reduce error rate in PN prescription. He noticed that the application of this method systematically improved the knowledge of senior clinical nurses and pediatric residents and decreased their mistakes in PN prescription (Brown, Garrison, & Hutchison, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Of the 26 CPOE interventions, 4 investigated the effects of CPOE without CDS compared with manual order entry 33,74,77,79 and reported a 44% to 88% reduction in prescribing errors. Five studies examined the effect of CPOE with CDS for multiple medications on inpatients 45,46,51,73,88 and found a 14% increase in errors to a 99% decrease in all types of errors.…”
Section: Data Synthesis For Specific Interventionsmentioning
confidence: 99%
“…[25][26][27] Specifically with PN prescribing, 4 small observational studies seem to show benefit in educating healthcare professionals. 23,[28][29][30] Each of these studies had small sample sizes and implemented a new PN order form or system along with physician education as a primary or secondary goal. All 4 studies concluded that the new form and education led to a substantial decrease in overall PN prescription errors, overutilization of PN, overfeeding, and/or associated cost.…”
Section: Strongmentioning
confidence: 99%
“…All 4 studies concluded that the new form and education led to a substantial decrease in overall PN prescription errors, overutilization of PN, overfeeding, and/or associated cost. 23,[28][29][30] Question 2. What is the maximum safe osmolarity of PN admixtures intended for peripheral vein administration?…”
Section: Strongmentioning
confidence: 99%